Effectiveness of Online Learning Implementation - Haedar Akib; Ahmad Amran; Muh. Darwis (Jurnal Office, 2021)
The implementation of online learning during covid-19 is a learning model that is now applied throughout Indonesia, as a form of government policy in an effort to reduce the chain of transmission of covid-19 in the country. This research was carried out with the aim of determining the level of effectiveness of the implementation of online learning during covid-19 (Study in the Department of Administrative Sciences, Faculty of Social Sciences and Law, State Universitas Negeri Makassar). This research uses a quantitative research approach with a descriptive type of research. The population in this study was students of the Department of Administrative Sciences, Faculty of Social Sciences, State University of Makassar, class of 2018 – 2020 with a total of 1,050 people.  The total sample was 15%, which was 157 people. Data collection is carried out with various techniques including observation, questionnaires, interviews and documentation. The data analysis technique used is percentage analysis. The results showed that the level of effectiveness of the implementation of online learning during Covid-19 (Study in the Department of Administrative Sciences, Faculty of Social Sciences and Law, Universitas Negeri Makassar) is classified as effective in terms of indicators of the presence of content or learning materials relevant to learning objectives, using appropriate learning methods, using learning media in various formats such as texts,  visual, video, multimedia, etc., and can occur synchronously or asynchronously.